Effects of implementation leadership of head nurses on nurses’ evidence-based pain management practices behavior - Lingyu Li; Quanru Wang; Ying Cao; Ling Liao; Binjie Yang; Min Tan (BMC Nursing)
Abstract Background Nurses’ evidence-based practice competencies were positively correlated with the implementation leadership (IL) of head nurses. However, there was no study to analyze the effect of IL on nurses’ evidence-based pain management practices (EBPMP) behavior from the hierarchical linear model (HLM) perspective. The objective of this study was to investigate the current status of head nurses’ IL and nurses’ EBPMP behavior, and to analyze the effects of head nurses’ IL on nurses’ EBPMP behavior. Methods In September 16, 2024 to September 30, 2024, nurses from 17 secondary and tertiary hospitals in Sichuan Province were selected by convenience sampling and investigated with the demographic characteristics, implementation leadership scale (ILS), and nurses’ evidence-based practice behavior questionnaire for pain management. The influence of the head nurses’ IL on nurses’ EBPMP behavior was analyzed using the HLM. Results A total of 2124 nurses were included in the analysis. The scores for head nurses’ IL were (M = 2.88, SD = 0.74) and nurses’ EBPMP behavior was (M = 3.98, SD = 0.76). The results of the HLM analysis showed that IL of head nurses had a positive predictive effect on nurses’ EBPMP behavior (p < 0.001); Nurses’ attitudes towards pain management and participation in pain education and training had a positive predictive effect on nurses’ EBPMP behavior (p < 0.001). Conclusions The EBPMP behavior of nurses and the IL of head nurses are at medium-high levels and still need further improvement. The IL of head nurses positively affected the nurses’ EBPMP behavior. Hospital managers can construct programs to improve the level of head nurses’ IL to facilitate the implementation of EBPMP and the implementation of more clinical evidence-based practices behavior. Clinical trial number Not applicable.